Investigation of biphenyl enamines for applications as p-type semiconductors - Matas Steponaitis; Vygintas Jankauskas; Egidijus Kamarauskas; Vida Malinauskienė; Smagul Karazhanov; Tadas Malinauskas; Vytautas Getautis (Royal Society Open Science, 2023)
Due to the ease of synthesis and the ability to easily tune properties, organic semiconductors are widely researched and used in many optoelectronic applications. Requirements such as thermal stability, appropriate energy levels and charge-carrier mobility have to be met in order to consider the suitability of an organic semiconductor for a specific application. Balancing of said properties is not a trivial task; often one characteristic is sacrificed to improve the other and therefore a search for well-balanced materials is necessary. Herein, seven new charge-transporting biphenyl-based enamine molecules are reported. The new materials were synthesized using a simple one-step reaction without the use of expensive transition metal catalysts. It was observed that subtle variations in the structure lead to notable changes in the properties. Materials exhibited high thermal stability and relatively high carrier drift mobility, reaching 2 × 10−2 cm2V−1 s−1 (for BE3) at strong electric fields. Based on the results, three materials show the potential to be applied in organic light emitting diodes and solar cells.